PERAN PROGRAM TENAGA KERJA MANDIRI (TKM) UNTUK PENGENTASAN KEMISKINAN DI KELURAHAN TUMBIHE, KABILA, BONE BOLANGO - Adelina Usman; Rauf A. Hatu; Sahrain Bumulo (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study aims to analyze the role of the Independent Workforce Program (Tenaga Kerja Mandiri/TKM) in poverty alleviation in Tumbihe Village, Kabila Subdistrict, Bone Bolango Regency. The program is an initiative by the Ministry of Manpower that focuses on job creation and community empowerment through training and provision of business facilities. The research employs a descriptive qualitative approach with five key informants, consisting of program beneficiaries, program facilitators, and village officials. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the TKM program contributes significantly to business capacity improvement (80%) and household income (average increase of 35%). In addition, the program strengthens economic independence and expands social networks among business actors. Based on Talcott Parsons' Structural Functionalism theory, TKM fulfills four main social functions: adaptation, goal attainment, integration, and pattern maintenance. The implication is that the implementation of the TKM program should be expanded to other areas with enhanced post-training mentoring to ensure more sustainable impacts on reducing local poverty levels